Structural Health Monitoring based on AR models and PZT sensors - De Oliveira, Mario Anderson; Vieira Filho, Jozué [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a new approach for damage detection in Structural Health Monitoring (SHM) systems, which is based on the Electromechanical Impedance (EMI) principle and Autoregressive (AR) models. Typical applications of EMI in SHM are based on computing the Frequency Response Function (FRF). In this work the procedure is based on the EMI principle but the results are determined through the coefficients of AR models, which are computed from the time response of PZT transducers bonded to the monitored structure, and acting as actuator and sensors at the same time. The procedure is based on exciting the PZT transducers using a wide band chirp signal and getting its time response. The AR models are obtained in both healthy and damaged conditions and used to compute statistics indexes. Practical tests were carried out in an aluminum plate and the results have demonstrated the effectiveness of the proposed method. © 2012 IEEE.
Keywords: Aluminum plates; AR models; Auto regressive models; CHIRP signals; Electromechanical impedance; Frequency response functions; New approaches; Practical tests; PZT sensors; PZT transducers; Structural health monitoring (SHM); Typical application; Wide-band; Damage detection; Frequency response; Piezoelectric transducers; Structural health monitoring; Sensors